EFEKTIVITAS PELAKSANAAN PROGRAM PENGEMBANGAN KEWIRAUSAHAAN USAHA MIKRO KECIL DAN MENENGAH OLEH DINAS KOPERASI USAHA MIKRO KECIL DAN MENENGAH KOTA PEKANBARU - Siti Nurjannah; Chalid Sahuri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Pekanbaru city government allegedly seeks to improve the well-being of thecommunity through the provision of a wide range of business opportunities in the field ofUMKM. How ever, these efforts are constrained due to capital, production techniques andmanagement capabilities are limited, relatively difficult marketing problems and low human.In this case Dinas Koperasi UMKM Pekanbaru City need to develop the UMKM, one ofwhich is to improve the quality of human resources UMKM and build the UMKM to have anentrepreneurial spirit. The problem in this study is how the condition Dinas Koperasi UMKMPekanbaru City in realizing the goal and what factors affect the effectiveness of the DinasKoperasi UMKM Pekanbaru City. This study aims to determine how the implementation ofUMKM entrepreneurship development program by Dinas Koperasi UMKM Pekanbaru City.And to determine the factors that influence the implementation of the development program.Theory concept that researcher use is effectiveness. This study uses qualitativeresearch methods to study descriptive data. In collecting data the researcher used interviestechniques, observation and documentation. By using key informan as a source ofinformation and as a source of triangulation techniques in testing the validity of the data.The results of this study indicate that the condition of the effectiveness of UMKMentrepreneurship development program Pekanbaru city is in the category yet effective, inwhich it is seen from the away goal achievement by Dinas Koperasi UMKM Pekanbaru City.Factors that affect organizational effectiveness are factors, environmental factors, laborfactors, managementpractices and policies. In which all these factors are very influential andshould be in line for the achieve affective implementation of development programsentrepreneurship UMKM by Dinas Koperasi UMKM Pekanbaru City.Keyword : Effectiveness, program Implementatio, Entrepreneurship